PENGEMBANGAN MODEL CRT DENGAN PENGUATAN KEARIFAN LOKAL UNTUK MENINGKATKAN KEMAMPUAN SISWA MENULIS ESAI DI SMA - Sinta Dewi Ginoga (LPPM Universitas Muhammadiyah Gorontalo, 2025)
This study aims to develop a Culturally Responsive Teaching (CRT) learning model that reinforces local wisdom to improve the essay writing skills of eleventh-grade students at SMA Negeri 2 Gorontalo. The study employed a Research and Development (R&D) method with a mixed methods approach, encompassing needs analysis, model design, expert validation, practicality testing, and effectiveness testing. Data were collected through observation, interviews, questionnaires, and essay writing tests (pretest and posttest). The results showed that the local wisdom-based CRT model had a high feasibility level, with expert validation results ranging from 85% to 90%. This model was also deemed highly practical by teachers (92%) and students (89%). The effectiveness test showed a significant improvement in students' essay writing skills, with the average score increasing from 67 in the pretest to 85 in the posttest, a 26.8% increase. The integration of local cultural values such as huyula, modutu, and bataso, as well as Gorontalo traditions and folklore, was proven to strengthen the development of ideas, argumentation, and the depth of students' writing content. Thus, the local wisdom-based CRT model is effective, practical, and suitable for use as an innovative, contextual, inclusive essay writing learning model that supports the implementation of the Independent Curriculum